Ranolazine exerted cardioprotection against doxorubicin-induced cardiotoxicity through inhibiting excessive autophagy in rats. (14th October 2021) - Arinno, A; Maneechote, C; Khuanjing, T; Chunchai, T; Prathumsap, N; Ongnok, B; Arunsak, B; Jaiwongkam, T; Kerdphoo, S; Shinlapawittayatorn, K; Chattipakorn, S C; Chattipakorn, N
Abstract: Background: Doxorubicin (Dox) is a highly effective chemotherapeutic agent for several malignancies. However, its cardiotoxicity and progressive heart failure are the most serious adverse effects that compromised its clinical use. Recently, ranolazine, the late sodium (Na+) current inhibitor for patients with chronic angina, has been suggested as a potential agent to treat early cardiotoxicity induced by antitumor drugs. In that single report, pretreatment with ranolazine improved cardiac function and decreased mortality rates in the Dox-treated rats, by decreasing oxidative stress and apoptosis. Nevertheless, its protective mechanisms on autophagy in the Dox-treated rats have never been elucidated. Purpose: We hypothesized that ranolazine exerts cardioprotection in the Dox-treated rats by improving left ventricular (LV) function and reducing cardiac injury though suppressing excessive autophagy. Methods: Male Wistar rats (n=24) received either normal saline solution (NSS, n=8) or Dox (3 mg/kg/day, i.p.) for 6 doses. Then, the Dox-treated rats were assigned to orally administered with either saline (n=8) or ranolazine (305 mg/kg/day, n=8) for 30 consecutive days. Following the treatment, the LV function, cardiac injury, and autophagy were determined. Results: Dox caused LV dysfunction as indicated by the decreased %LV ejection fraction (LVEF) and the increased serum cardiac troponin-I (cTn-I) levels (Fig. 1A). In addition, Dox induced excessive autophagy by increasing Beclin-1, p62, and light chain 3-II/I (LC3II/I) protein expressions (Fig. 1B). Treatment with ranolazine attenuated autophagic-related proteins (Beclin-1, p62, and LC3II/I), and improved LV function (Fig. 1A-B). Conclusion: Ranolazine exerted cardioprotection in the Dox-treated rats through suppressing autophagic-regulatory proteins, suggesting its potential cardioprotective roles as a concomitant therapy for cancer patients receiving Dox. FUNDunding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): the NSTDA Research Chair grant from the National Science and Technology Development Agency Thailand and the National Research Council of Thailand